EFEKTIVITAS PEMBERLAKUAN SURAT IZIN MENGEMUDI TERHADAP PENGEMUDI DIBAWAH UMUR KECAMATAN KALIDERES, JAKARTA BARAT - Gladys Natalie Aurielle Sirait; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
The requirements for motorcycle drivers are regulated in Law No. 22 of 2009 concerning Road Traffic and Transportation, namely in Article 80 which reads "everyone who drives a motorized vehicle on the road is required to have a driving license in accordance with the type of motorized vehicle being driven". This writing raises the issue of the effectiveness of the application of a driving license to underage drivers, especially in Kalidere District, West Jakarta. However, this has not been achieved optimally, it can be seen in the phenomenon of the practice of underage drivers who are still commonly found on Highways, especially in Kalideres District, West Jakarta. This writing uses a normativeempirical method, namely where data collection is carried out by direct observation in the field through interviews, secondary data collection is carried out first before conducting interviews. With the increasing number of motorized vehicles, the facts show that many children are actually not old enough to drive a motorized vehicle. Whereas Law No. 22 of 2009 has regulated the problem of motorized vehicle drivers. Motorcycles have become an inseparable part of the lives of Indonesian people. Until 2016 the number of motorcycles in Indonesia reached 85 million vehicles. However, the large use of motorcycles in Indonesia has not been matched by awareness of driving safety